Effect of plasma processing and storage on microparticle abundance, nitric oxide scavenging, and vasoactivity. (13th April 2019) - Rogers, Stephen C.; Moynihan, Francis T.; McDonough, Ryan; Timm, David D.; Hovmand‐Warner, Eyvind; Frazier, Elfaridah; Thomas, Kimberly A.; Spinella, Philip C.; Doctor, Allan
Abstract : BACKGROUND: We set out to define the impact of collection, processing, and storage on plasma product microparticle (MP) abundance, potential for nitric oxide (NO) scavenging, and vasoactivity. STUDY DESIGN AND METHODS: Three currently US licensed products were tested: liquid plasma (LP), fresh frozen plasma (FFP), and solvent detergent plasma (SDP), along with a product under development, spray‐dried solvent detergent plasma (SD‐SDP) with/without beads. Vasoactivity was assessed in vitro using rabbit aortic vascular rings; MP abundance was determined by flow cytometry; and NO scavenging capacity/rate was determined using a biochemical NO consumption assay. All samples were analyzed unprocessed and following centrifugation at two speeds (2, 500× g to remove platelets, and 25, 000× g to remove microparticles). RESULTS: Significant differences in vasoactivity were observed, with SD‐SDP minus beads demonstrating the greatest constriction and FFP the lowest constriction response. All products exhibited the same total NO scavenging capacity; however, significant differences were observed in the maximal rate of scavenging, with SD‐SDP minus beads and FFP reacting fastest and SDP the slowest. Across all products, platelet and microparticle depletion had no effect on vasoactivity or NO scavenging (total or rate). Microparticles (RBC derived) were found only in FFP and LP, with relative abundance (LP > FFP). Additionally, storage had no effect on total or RBC‐derived MP abundance, NO scavenging, or vasoactivity. CONCLUSION: Although vasoactivity differed between plasma products, we did not find similar differences in either total or RBC‐derived MP abundance or NO scavenging capacity/rate.